MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN DISIPLIN KERJA DAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL MEDIASI DI BAGIAN KEUANGAN RS X - Rabia Nur Hania; Denny Bernardus (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2019)
Human resources is a device that is used by every organization or company to achieve it’s goal. The success of an organization or company is the result of maximum performance of on employee in that company, the company will not run or succed if the employee cannot work well, therefore the development og good human resource must be created by a company. The purpose of this research is to evaluate the influence of motivation on employee performance, motivation on work discipline, motivation on employee engagement, work discipline on employee performance, employee engagement on employee performance, motivation on employee performance is mediated by work discipline, and motivation on employee performance is mediated by employee engagement. This research was conducted in the financial department of RS X with the total population and sample of 49 people. The method that is used in this research is quantitative by using primary and secondary data types. Data collection technique is by using questionnaire. Data analysis methods use SEM-PLS. Outcome of the research shows that motivational variable have positive, significant effect towards employees’ performance, work discipline and employee engagement. Work discipline variable mediated connect to employes’ performance. Work discipline variable mediates connection between motivational and employees’ performance, cause a positive and significant effect. Likewise with employee engagement variable mediate the relationship between motivation on employee performance and influence positive and significant. Keywords : Employee Engagement,Employee Performance,Motivation, Work Discipline